Spiritual wellness among undergraduate college students - Patneaude, Anne B., author; Kees, Nathalie, advisor; Timpson, William M., committee member; Most, David, committee member; Kennedy, Cathy, committee member (Colorado State University. Libraries, 2006)
The purpose of this research study was to explore the spiritual wellness of undergraduate college students. More specifically, the aim of this study was to assess the spiritual beliefs, views, and practices of undergraduate college students and the influence of spiritual wellness on the other five dimensions of wellness including emotional, physical, social, intellectual, and occupational. In turn, this should provide valuable information to campus community members for the development of programs and services in an effort to meet the spiritual wellness needs of this target group. A self-report questionnaire was developed specifically to collect measures of spirituality and demographic information. The sample consisted of 303 undergraduate students who were randomly selected from the 2005-2006 Colorado State University Directory. Findings showed that spiritual wellness plays an important part in the lives of college students and the decisions they make on a daily basis regarding the other dimensions of wellness. Students are active in nurturing spirituality in a variety of ways such as volunteer activities for personal and social helping, personal reflection, and prayer. Over half of the students would like the university to offer a variety of learning experiences to help develop spiritual wellness. At the same time, some students say that it is not the responsibility of the university. The results further indicated differences across gender, age, ethnicity, and year in school with regards to views on spirituality and the influence spiritual wellness has on the other wellness dimensions. This study should help to expand the body of literature in the area of spiritual wellness among college students. Further research is recommended to examine student spiritual wellness and the influence spirituality has on the other dimensions of wellness.
Keywords: health education; religion; higher education